Fast and slow light generated by surface plasmon wave and gold grating coupling effects - Amiri, Iraj Sadegh; Ariannejad, Mohammad Mahdi; Tajdidzadeh, Mojgan; Sorger, Volker J.; Ling, Xi; Yupapin, Preecha Promphan (Springer Verlag, 2018)
We present here the results of a simulation of the effect of gold and graphene coatings on silicon micro-ring resonators. We studied the effect of different radii of graphene on the time delay, from which one an interesting aspect of light pulse behaviors, such as fast light, was numerically investigated. The obtained results indicate that the time delay can be varied, which is in good agreement with theoretical predictions. Fast and slow light pulse trains can be obtained by modifying the throughput port, which forms the gold grating length. The temporal gaps between the fast and slow light in the used graphene and gold are 140 and 168 fs, respectively, which can be tuned by varying the radius or grating length. The obtained results show that such a device may be useful in applications requiring fast and slow light pulse train pairs, such as optical switching, sensors, communications, and security applications.